Salicornia ramosissima: secondary metabolites and testicular protection induced by ethanol extract - Ferreira, Daniela (2013)
The structure and spectroscopic characterization of the isolated compounds from etanol and dichloromethane extracts (PUFA omega3 ethylated, sterol and a rare wax) will be presented and discussed. Concerning the effect of ethanolic extract on mice testicular tissue under carbon tetrachloride exposure, it was clearly demonstrated that ethanol extract had a protective effect.